Female Social and Cultural Roles Concerning Syphilis in Post-Revolutionary Mexico, 1910-1940 - Aranda, Crystal (Kansas State University. Dept. of History, 2011)
This study concerning health reform in Mexico focuses on the effects of gender roles on syphilis epidemics in Mexico, 1910-1940. Accepted gender roles of Mexican males and females, especially those pertaining to femininity significantly impacted Mexico's tolerance of venereal diseases, such as syphilis. In addition to these ideals Mexico's bout with syphilis is a direct correlation to the lenient and accommodating attitude of the Mexican government, military and religious institutions, as well as its cultural and social communities toward syphilis. This study also focuses geographically on the nation's capitol Mexico City, as it was and still is the heart of Mexico. Between 1910 and 1940, reforms and laws were first instituted in Mexico City and as a result were more strictly enforced in the capitol city. Additionally, the densely populated urban environment of Mexico City provided a more diverse populace lending significance to this study in that a more complete analysis of the Mexican population concerning syphilis was conducted. By understanding health reform, prostitution, and venereal disease in Mexico as an interrelated subject, I analyze three threads of inquiry beginning with the assigned and preconceived stereotypes of women, how multiple groups in Mexican society approached sexual health and reform, and the geographic distribution of syphilis within Mexico City. Study of these interrelated factors will provide effective framework for a more complete understanding of how health reform reestablished and challenged expected gender roles and social norms in Mexico, 1910 and 1940.
Keywords: Gender roles; Mexico; Syphilis; Health reforms; Prostitution; Post-Revolutionary Mexico